Exploring the impact of coaching on employee performance and organization effectiveness: A conceptual study - Herdiansah Abdul Karim; Nor Azma Rahlin (Universiti Malaysia Sabah, 2024)
In an era marked by rapid technological advancements, shifting demographics, and evolving citizen expectations, government agencies must adapt, innovate, and deliver services efficiently and effectively. In this context, coaching emerges as a powerful tool to empower government. Thus, this conceptual study explores the critical concepts of coaching and synthesizes findings related to coaching's impact on individual employees and organizational performance. A systematic search in bibliographic databases such as PubMed, PsycINFO, ERIC, Web of Science, and Google Scholar was conducted to identify relevant studies. Systematic review on full-text articles from 2000 to 2023 using keywords, such as coaching, coaching program, employee performance, and organizational performance. Many studies reveal that coaching positively impacts employees in several ways. Coaching provides many benefits, including improving employee engagement, skills, performance, confidence, and self-efficacy. It also accelerates learning, develops leadership abilities, enhances problem solving, and fosters innovation. Additionally, coaching supports talent retention and development while fostering a positive organizational culture. In the civil service, coaching aids in skill development, career advancement, addressing weaknesses, adapting to change, and managing stress, resulting in overall performance improvement. This study provides valuable insights and contributions to advancing both academic understanding and practical application in this critical area of organizational development and human resource management.